Pengaruh Gaya Kepemimpinan, Kompetensi, dan Kompensasi terhadap Kinerja Pegawai serta Dampaknya pada Kinerja Organisasi di Kementerian Pertanian - Sugito Efendi; Suwardi Suwardi (FOCUS, 2020)
This study aims to analyze the influence of leadership style, competence, compensation on employee performance and the impact on organizational performance on the employees of the Directorate General of Agricultural Infrastructure and Facilities. This study used a survey method by distributing questionnaires to employees of the Directorate General of Agricultural Infrastructure and Facilities. As the respondent. This research method uses quantitative methods with technical analysis of Structural Equation Modeling (SEM) with the AMOS version 22 application. The research sample used in this study were 158 respondents. The results showed that leadership style, competence and compensation directly had a positive and significant effect on employee performance. Leadership style, competence and compensation directly have a positive and significant effect on organizational performance. Leadership style, competence and compensation indirectly have a positive and significant effect on organizational performance through employee performance.